The Effect of Using Physics Education Technology (PhET) Simulation Media to Enhance Students’ Motivation and Problem-Solving Skills in Learning Physics - Anggi Susilawati; Yusrizal Yusrizal; A. Halim; Muhammad Syukri; Ibnu Khaldun; Susanna Susanna (Jurnal Penelitian Pendidikan IPA, 2022)
One of the demands of 21st-century skills is problem-solving skills, to have good solving skills, one must have good learning success factors, such as learning motivation. In fact, from the results of observations and interviews conducted at SMA Negeri 2 Darul Makmur, it was found that the motivation and problem-solving skills of students were still low. The purpose of this research is for investigating the effect of using Physics Education Technology (PhET) simulation media to enhance students’ motivation and problem-solving skills in learning physic. This research used a quasi-experiment quantitative approach with Non-Equivalent Control Group Design. The population of this research was students of Grade XII MIA as many as 57 students. There were 50 students taken by random sampling. The instrument was questioned in the form of an essay and questionnaire by the Likert scale. The data of this research was analyzed by average test, N-gain, and independent-sample t-test. The result showed that the average score of motivation study in experiment class is in the high categorize and in the control class is in the low categorize, while N-gain score problem-solving skill for experiment class is in the high categorize and in control class is in the medium categorize. Moreover, based on an independent sample test is obtained that there is a significant difference between for problem-solving motivation and skill, this is strengthened by the positive response of students using media simulation PhET in learning. It can be concluded conveyed that media simulation of Physics Education and Technology (PhET) in learning physic can enhance students’ motivation and problem-solving skills